2021
DOI: 10.3390/cancers13174439
|View full text |Cite
|
Sign up to set email alerts
|

Leukoplakia in the Oral Cavity and Oral Microbiota: A Comprehensive Review

Abstract: We reviewed the current published literature on the impact of oral microbiota on oral cavity leukoplakia (OLK), aiming at clarifying its role in disease transformation. The analysis unveiled that bacterial richness and diversity in the oral cavity tend to be decreased in OLK compared to healthy controls, with a reduction in the prevalent commensals, such as Streptococci, and elevation of anaerobes. Moreover, Fusobacterium nucleatum, Porphyromonas gingivalis and Prevotella intermedia are recurrent findings, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…For an individual microbiome and its ability to produce ACH, poor oral hygiene, dysbiotic microflora (independent risk factor for oropharyngeal cancer), smoking and drinking alcohol increase the production of ACH [ 146 , 147 , 148 , 152 ]. Severe leukoplakia and insufficient oral hygiene promote a dysbiotic, fungal microflora [ 146 , 153 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For an individual microbiome and its ability to produce ACH, poor oral hygiene, dysbiotic microflora (independent risk factor for oropharyngeal cancer), smoking and drinking alcohol increase the production of ACH [ 146 , 147 , 148 , 152 ]. Severe leukoplakia and insufficient oral hygiene promote a dysbiotic, fungal microflora [ 146 , 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other potent producers of ACH are Rothia mucilaginosa , Neisseria spp., Streptococcus spp. [ 152 , 154 ]. A role of bacteria in carcinogenesis relies on the expression of alcohol dehydrogenases and the lack of ability to produce functional acetaldehyde dehydrogenases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral cancer is a complex and multifactorial disease associated with different risk factors that can be modified such as alcohol consumption, tobacco use, a low fiber diet [4] and HPV infection with a 30-fold increased risk for individuals who both smoke and drink heavily. Furthermore, oral dysbiosis has been linked to periodontal disease and was reported to be a possible etiologic factor for oral squamous cell carcinoma, either isolated or synergistic with other agents [5]. It was reported that OC has been associated with increased oxidative stress, as lipid peroxidation, and reduced antioxidants were reported in patients suffering from stage II, III and IV oral cancer [6] as well as autophagy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to smoking and drinking, oral bacteria have been reported to be associated with oral cancer 2 , 5 , 6 . The involvement of oral bacteria has also attracted attention in terms of malignant changes from oral potentially malignant disorders (OPMD) to OSCC 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%